2018
DOI: 10.3390/ph11030067
|View full text |Cite
|
Sign up to set email alerts
|

Looking for Novel Capsid Protein Multimerization Inhibitors of Feline Immunodeficiency Virus

Abstract: Feline immunodeficiency virus (FIV) is a member of the retroviridae family of viruses. It causes acquired immunodeficiency syndrome (AIDS) in worldwide domestic and non-domestic cats and is a cause of an important veterinary issue. The genome organization of FIV and the clinical characteristics of the disease caused by FIV are similar to human immunodeficiency virus (HIV). Both viruses infect T lymphocytes, monocytes, and macrophages, with a similar replication cycle in infected cells. Thus, the infection of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…The diffusion behavior of the protein is altered later, when it is complexed with an increased number of unlabeled ligand molecules. The binding affinity ( K d ) of the ligand can be determined by obtaining the titration curves [ 31 ]. By definition, the dissociation constant ( K d ) refers to the concentration of ligand at which half of the ligand binding sites on the protein are occupied by the ligand molecules [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…The diffusion behavior of the protein is altered later, when it is complexed with an increased number of unlabeled ligand molecules. The binding affinity ( K d ) of the ligand can be determined by obtaining the titration curves [ 31 ]. By definition, the dissociation constant ( K d ) refers to the concentration of ligand at which half of the ligand binding sites on the protein are occupied by the ligand molecules [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Even so, both structures are still considered Pan-Assay Interference Compounds (PAINS) because they also have groupings that can function as Michael acceptors with these able to nonspecific toxicity. However, despite extensive efforts, we were unable to identify what these nonspecific activities are for the compounds used here [ 14 , 27 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, GS-6207 binds at the CA/CA interface within HIV-1 CA hexamers and has been optimized from lead molecules using the structural data available on these hexamers [14,52,53]. For FIV, assembly inhibitors have recently been identified that bind the same region of CA, which seems to be similarly able to interact with feline nucleoporins [42,54] and thus represent an interesting therapeutic target. Obtaining structural data on FIV CA oligomers will therefore be of prime importance for the optimization of these compounds towards efficient anti-FIV molecules.…”
Section: Fiv Camentioning
confidence: 99%